THE EFFECT OF THINK-PAIR-SHARE (TPS) STRATEGY IN READING COMPREHENSION BY ENGLISH DEPARTMENT STUDENTS AT FKIP UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - Dumaris E. Silalahi (STKIP PGRI Jombang, 2015)
this research intends to investigate the effect of Think-Pare-Share (TPS) strategy in reading comprehension by the third semester of English Department Studentsat FKIP Universitas HKBP NommensenPematangsiantar. The subjects of the research are 30 students as experiment and control group. This research applies quantitative research method in analyzing the data which refers to the number in the form of students’ value as the measurement of students’reading comprehension. This research conducted into the third semester at academic year 2014-2015 as the population and the sample is class A and B. based on the data analysis, the researcher finds out the effect of TPS strategy in students’ reading comprehension by these research findings show that the mean of students’ score in experiment class is 41,73 than in control class is 11, 34. There are 28 students who get the highest score in experiment class. They get the mean score more than 55. 65 or 93% students get high score while in control class there are 25 students who get the 41, 34 mean score or 83% as the highest score